Reduced bacterial adhesion on ceramics used for arthroplasty applications. Issue 3 (March 2018) - Sorrentino, Rita; Cochis, Andrea; Azzimonti, Barbara; Caravaca, Carlos; Chevalier, Jerome; Kuntz, Meinhard; Porporati, Alessandro Alan; Streicher, Robert Michael; Rimondini, Lia
Abstract: Orthopaedic-implant-related infections are challenging for clinicians: despite progresses in surgical procedures, the mortality rate of patients experiencing periprosthetic joint infections still ranges from 10 to 18%. Generally, infection starts when planktonic bacteria arising from surgery escape immunological surveillance adhering onto implant surface. Bacterial adhesion depends mainly on material's intrinsic surface features depending on its chemical and physical properties. This study compares materials used for bearings of total hip arthroplasty, advanced ceramics (alumina and zirconia-platelet toughened alumina composites), metals (cobalt–chromium–molybdenum alloy) and polymers (highly cross-linked polyethylene), in terms of wettability and protein adsorption. Materials were infected with Staphylococcus aureus and Staphylococcus epidermidis biofilm for 24 or 48 h. Bacterial adhesion properties were evaluated by means of biofilm viability, morphology, and thickness, in a worst-case surface roughness condition. Thanks to selective protein adsorption, bioceramics reduced bacterial adhesion and subsequent biofilm formation more effectively in comparison with metal and polymer surfaces.